The road to Berlin - Erickson, John, 1929-2002. (New Haven, Conn. : Yale University Press, 1999)
"The follow-up to the acclaimed The Road to Stalingrad tells the compelling story of the Red Army's epic struggle to drive the Germans out of Russia and back to Berlin. Using Soviet, German, and Eastern European primary sources, John Erickson describes fighting and hardship on an almost unimaginable scale. The detailed narrative covers battles on all the fronts. The inside information on the Soviet system of war reveals how, under maximum stress, the Russian army achieved near-impossible feats in the field and the factories. All the diplomatic moves and counter-moves, including the all-important conferences at Tehran and Yalta, also come vividly alive"--Publisher's description.
"Surrender is ruled out" : the end at Stalingrad -- The duel in the south : February-March 1943 -- Breaking the equilibrium : Kursk and its aftermath -- The drive to the western frontiers : October 1943-March 1944 -- Breaking the back of the Wehrmacht : April-August 1944 -- Soviet liberation, Soviet conquest : August-December 1944 -- The assault on the Reich : January-March 1945 -- No time to die : April-May 1945.
Keywords: Stalin, Joseph, -- 1878-1953.; Stalin, Joseph, -- 1878-1953; 1939-1945; World War, 1939-1945 -- Campaigns -- Eastern Front; Guerre mondiale, 1939-1945 -- Campagnes et batailles -- Front oriental; Military campaigns; Eastern Front (World War (1939-1945))